1987
DOI: 10.1148/radiology.164.1.3588899
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic varicoceles: feasibility of percutaneous sclerotherapy.

Abstract: Percutaneous retrograde venography was performed in 717 patients with a left-sided idiopathic varicocele. In 674 (94.0%), testicular (internal spermatic) vein insufficiency was proved by contrast medium reflux from the left renal vein into the testicular vein, down to the pampiniform plexus. The different venographic patterns of the testicular veins were classified into seven basic types. Five of these, comprising 624 patients, had incompetent or missing valves all along the trunk of the testicular vein. In 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 0 publications
2
18
0
3
Order By: Relevance
“…Although the recurrence rate of laparoscopic procedure is reported to be lower than inguinal varicocelectomy and embolization (0-2 % compared to 15 % in inguinal and 7-16 % in embolization) [20][21][22][23][24], this procedure presents higher complication rate compared to embolization [21,25]. Contradictorily, Silvera et al reported that laparoscopic procedure has no complications; however, this study presented a limited cohort of 20 patients.…”
Section: Discussionmentioning
confidence: 77%
“…Although the recurrence rate of laparoscopic procedure is reported to be lower than inguinal varicocelectomy and embolization (0-2 % compared to 15 % in inguinal and 7-16 % in embolization) [20][21][22][23][24], this procedure presents higher complication rate compared to embolization [21,25]. Contradictorily, Silvera et al reported that laparoscopic procedure has no complications; however, this study presented a limited cohort of 20 patients.…”
Section: Discussionmentioning
confidence: 77%
“…In 1978 Iaccarino [20] first described the possibility of combining the diagnostic procedure of spermatic venography with definitive occlusion of the spermatic vein. In the past 20 years, several authors have published results of percutaneous occlusion of varicocele [21,22] and percutaneous transcatheter embolization using various embolic materials for the treatment of varicocele is now widely performed [16,17]. Since 1984 we have been convinced that retrograde phlebography plays a precise role in better defining the anatomy of the internal spermatic veins [14].…”
Section: Discussionmentioning
confidence: 99%
“…Varicoceles were classified according to an adapted version of Dubin and Amelar [26] in subclinical: grade 1 (small), grade 2 (moderate), and grade 3 (large). Phlebographic classification of the left spermatic vein insufficiency was done according to the Bähren et al [27,28] types and for the right spermatic vein according to Siegel et al [29].…”
Section: Comparability Of Both Study Populationsmentioning
confidence: 99%